The Role of Counselors in Building Students' Social Awareness so as not to be provoked by Demonstration Situations - Azizah, AmaliaAulia Nur (PT. Anagata Sembagi Education, 2025)
This study examines the role of counselors in building students' social awareness so that they are not easily provoked by demonstration situations. The background of this study departs from the phenomenon of student demonstrations which often shift from a forum for expressing aspirations to a place for provocation and destructive actions. Using a literature review approach, this study highlights the contribution of counselors through individual, group, psychoeducation, and cross-party collaboration counseling services. The results of the study show that counselors have a central role in fostering empathy, solidarity, self-control, and critical thinking in students, which serve as a filter against mass provocations. Effective counselor strategies include open communication, peer counseling, and character education and social-emotional skills programs. However, there are still obstacles in the form of limited resources, lack of policy support, and student resistance to counseling interventions. Therefore, strengthening counselor capacity, institutional policy support, and integrating technology-based strategies are key to increasing the effectiveness of counseling services. This article emphasizes the urgency of optimizing the role of counselors in building students' social awareness, in order to create an educational environment that is safer, more inclusive, and resilient to provocation